Power Function Solutions of Iterative Functional Differential Equations with Some Conditions - มะเวชะ (ตาลวงค์), ศุกระวรรณ (KKU Science Journal, 2013)
Iterative functional differential equations occur in many problems of physics and other sciences. This article is concerned with three equations x(n) (z) = Azj ( x[m] (z) )k, x(n) (z) = A ( x[mi] (qiz) )ki and a more general equation ( x(ni) (piz) )Ni = Azj ( x[mi] (qiz) )Mi . We consider the existence of power solutions of the form x(z) = z for those three equations with given conditions.